Contesting post-racialism: Conflicted churches in the United States and South Africa - Pretorius, Helgard (Stellenbosch Theological Journal, 2016)
Contesting post-racialism: Conflicted churches in the United States and South Africa by R Drew Smith, William Ackah, Anthony G Reddie, and Rothney S Tshaka (Eds) 2015, University Press of Mississippi, Jackson ISBN: 9781628462005